"Pigments of Life", Molecules Well Suited to Investigate Metal–Ligand Symmetry‐Restricted Covalency. Issue 27 (6th July 2018) - Casarin, Maurizio; Carlotto, Silvia
Abstract : First principle quantum mechanical calculations are able to provide results comparable in accuracy to experimental measurements; moreover, it is unanimously recognized that the information they afford is often more accessible than that provided by conventional spectroscopy. Here we focus on the modelling and, possibly, on the prediction of X‐ray absorption spectroscopy (XAS) evidences at the L2, 3 ‐edge of first row transition metal (M) macrocyclic complexes, which have been attracting an increasing interest because of their widespread technological applications. The comparison of homogeneous theoretical results with those achieved for complexes of the same central M ions but different ligands ultimately confirms the role played by the M chemical environment, the M electronic configuration and the M oxidation number in determining the appearance of L2, 3 XAS features, which may be then exploited as a M fingerprint. Abstract : The DFT/ROCIS method has been exploited to model and predict L2, 3‐edge XAS features of first‐row transition metal macrocyclic complexes.